Targeted and untargeted metabolomic approach for GDM diagnosis - Burzynska-Pedziwiatr, Izabela; Dudzik, Danuta; Sansone, Anna; Malachowska, Beata; Zieleniak, Andrzej; Zurawska-Klis, Monika; Ferreri, Carla; Chatgilialoglu, Chryssostomos; Cypryk, Katarzyna; Wozniak, Lucyna A.; Markuszewski, Michal J.; Bukowiecka-Matusiak, Malgorzata (Frontiers in Molecular Biosciences, 2023)
Gestational diabetes mellitus (GDM) is a disorder which manifests itself for the first-time during pregnancy and is mostly connected with glucose metabolism It is also known, that fatty acid profile changes both, in erythrocyte membranes and in the plasma could be associated with obesity and insulin resistance. These factors can lead to a diabetes development. In the reported study, we applied the untargeted analysis of plasma in GDM versus standard glucose tolerance (NGT) women to identify the differences in metabolomic profile between those groups. We found a higher level of 2-hydroxybutyric and 3-hydroxybutyric acids. Both secondary metabolites are connected with impairments of glucose metabolism, however, hey are products of different metabolic pathways. Additionally, we applied lipidomic profiling using gas chromatography to examine the fatty acid composition of cholesteryl esters in the plasma of GDM patients. Among the 14 measured fatty acids characterizing the representative plasma lipidomic cluster, myristic, oleic, arachidonic and α-linoleic acids revealed statistically significant changes. Concentrations of both myristic acid, one of the saturated fatty acids (SFA) and oleic acid, which belongs to monounsaturated fatty acids (MUFA), tend to decrease in GDM patients. In the case of polyunsaturated fatty acids (PUFA), some of them tend to increase (e.g., arachidonic), and some of them tend to decrease (e.g., α-linolenic). Based on our results, we postulate the importance of hydroxybutyric acid derivatives, cholesteryl esters composition and the oleic acid diminution in the pathophysiology of GDM. However, metabolic alterations that lead to the onset of GDM are complex and therefore, further large sample size studies are needed to confirm our observations.